The Concept of Sustainable Development: the Basis for the Emergence of Integrated Reporting of the Enterprise - K. V. Bezverkhiy (Naukovij Vìsnik Nacìonalʹnoï Akademìï Statistiki, Oblìku ta Auditu, 2018)
The sustainable development of societies, countries, economic sectors or business enterprises is based on the assumption that economic growth, production and consumption has the limitations imposed by the possibility for rehabilitating ecological systems. Issues of the rational use of resources form the conceptual framework for the sustainable development. But the emergence of information support in form of integrated reporting of the enterprise causes much debate in the theoretical and practical field. The purpose of the study is to analyze the evolution of the provisions of the sustainable development concept and identify the preconditions for the emergence of integrated reporting of the enterprise.